Dysaethria moza ... - Beljaev, Еvgeniy A.; Titova, Olga L. (Zenodo, 2023)
Dysaethria moza (Butler) (Fig. 3) Dysaethria moza: iNaturalist (2022a): GBIF occurrence 2465091989 (Sokol). Material examined. 10 ♂, 4 ♀, Sokhonda mount., 20, 21, 23, 26.VII.2019; 1 ♀, Razdolnoe, 26.VII.2019; 1 ♂, 3 ♀, S Kholmsk: 21.VII, 03, 05, 11.IX.2021. Distribution. Russia (S RFE: S * Sakhalin, S Kurils—Kunashir), Japan (from Hokkaido on the north up to Tsushima on the west and Amami Oshima on the south), south of North Korea, South Korea, N China (Shaanxi — BOLD Sample ID: BC ZSM Lep 29750, as “ Epiplema AH 01Ch”; GBIF occurrence 885130484). Remarks. In the GBIF, Andrei Humala (Forest Research Institute, Karelian Centre of Russian Academy of Sciences, Petrozavodsk, Russia) posted a photo of D. moza, taken 13.VII.2009 at Sokol village (Dolinskii distr., 47.2542º N, 142.8068º E) near the Okhotian coast of Sakhalin (iNaturalist 2022a). This locality is placed much to the northeast from our collecting places that indicates a wide distribution of this species in the southern part of the island. The finding ... : Published as part of Beljaev, Еvgeniy A. & Titova, Olga L., 2023, New data on geometroid moths (Lepidoptera: Geometroidea: Uraniidae and Geometridae) from Sakhalin and Moneron islands with notes on their taxonomy distribution and ecology, pp. 1-41 in Zootaxa 5369 (1) on page 6, DOI: 10.11646/zootaxa.5369.1.1, http://zenodo.org/record/10147411 ...